Understanding the crisis in India. - War Resisters International; Indians For Democracy;:::Creator::::::::::::; Devi Prasad:::Contributor::::::::::::
Poster promoting a talk on the current situation and crisis in India by Devi Prasad who worked with Mahatma Gandhi during the Indian Independence Movement and with Jayaprakash Narayan in the Sarvodaya movement. The talk was held at Berkeley Friends Meeting House.